Recurrent Primary Focal Segmental Glomerulosclerosis Managed With Intensified Plasma Exchange and Concomitant Monitoring of Soluble Urokinase-Type Plasminogen Activator Receptor–Mediated Podocyte β3-integrin Activation. Issue 12 (December 2015) - Staeck, Oliver; Slowinski, Torsten; Lieker, Ina; Wu, Kaiyin; Rudolph, Birgit; Schmidt, Danilo; Brakemeier, Susanne; Neumayer, Hans-Hellmut; Wei, Changli; Reiser, Jochen; Budde, Klemens; Halleck, Fabian; et al.
Abstract : Background: Primary focal segmental glomerulosclerosis (FSGS) often causes nephrotic proteinuria and frequently results in end-stage renal disease and recurrence after kidney transplantation. Recent studies describe soluble urokinase-type plasminogen activator receptor (suPAR) as a circulating factor implicated in FSGS. Methods: This single-center study included 12 adult patients with histologically proven primary FSGS (n = 2) or recurrent FSGS after transplantation (n = 10). The effect of plasma exchange (PE) on clinical outcome, suPAR levels, and in vitro podocyte β3-integrin activation was investigated over a median of 11 (6-18) sessions of PE. Results: The course of treatment was monitored in a total of 70 sessions of PE, which partly eliminated suPAR, with a mean reduction of 37 ± 12% of serum concentration per session. However, a substantial rebound was observed between sessions, with suPAR levels reaching 99 ± 22% of the pretreatment levels after a median of 4 days. Podocyte β3-integrin activation dropped significantly after PE but rebounded within 4 days concomitant with a rising suPAR level. In 11 of 12 patients, multimodal treatment (including extensive PE) reduced proteinuria significantly (from 5.3 [2.0-7.8] to 1.0 [0.4-1.6] g/d), indicating clinical efficacy of the therapy. One patient suffered allograft loss due to FSGS recurrence. A persisting response was independent of a lasting reduction in the level of total suPAR because there was no sustained significant change in suPAR levels before and after the course of intensified treatment (3814 ± 908 to 3595 ± 521 pg/mL; P = 0.496). Conclusions: We conclude that multimodal therapy including extensive PE was associated with stabilization of recurrent FSGS and a temporary lowering of plasma suPAR as well as podocyte β3-integrin activation. Whether a sustained lowering of total suPAR results in further improved outcomes requires additional study. Abstract : The etiology and treatment of de novo or recurrent FSGS is elusive. This study associates clearance of suPAR and podocyte A3-integrin and plasma exchange with stabilization of recurrent FSGS.